About the experience of the Kazakh university of economics, finance and international trade in the development of internationalization processes through Erasmus + projects - Abdymanapov, Sarsengali; Toxanova, Aigul; Kapenova, Asemgul (KAZGUU University, Nazarbayev University, 2018)
The internationalization of higher education creates new opportunities, contributes to increasing the accessibility and quality of higher education and the introduction of innovative work processes in higher education systems. Relying on the achievements of international cooperation, internationalization, in turn, contributes to its strengthening. The strategy of internationalization of KazUEFMT is developed in accordance with the strategy of academic mobility in the Republic of Kazakhstan for 2012-2020, as well as the documents of the Organization for Economic Cooperation and Development (OECD).
Keywords: ERASMUS +; Organization for Economic Cooperation and Development (OECD); academic mobility; Academic Integrity